Polymer-based materials and composites--synthesis, assembly, properties and applications : symposium held November 29-December 3, Boston, Massachusetts, U.S.A. - Materials Research Society. Meeting (2010 : Boston, Mass.); Cheng, Z.-Y; Materials Research Society. Meeting (Fall 2010 : Boston, Mass.); Symposium HH, "Polymer-Based Materials and Composites--Synthesis, Assembly and Applications" (2010 : Boston, Mass.); Symposium II, "Polymer-Based Nanocomposites" (2010 : Boston, Mass.); Symposium JJ, "Nanostructured Polymeric Materials--Synthesis and Assembly" (2010 : Boston, Mass.) (Warrensdale, Pa. : Materials Research Society ; New York, N.Y : Cambridge University Press)
Includes bibliographical references and indexes